Inventory of Pests and Intensity of Fruit Fly Attacks (Bactrocera dorsalis) on Curly Red Chili Plants (Capsicum annum L.) in Sido Luhur Farmer Group of Cabeyan Village - Endang Suprapti; Agus Budiyono; Tyas Soemarah Kurnia Dewi; Daryanti; Wiyono; Dicky Hermawan (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2022)
Curly red chili (Capsicum annum L.) is a horticultural plant that has high economic value. So many people are cultivating it. Chili plants are susceptible to the attack of Plant Disrupting Organisms (OPT) which can decrease the production yield and quality of chili harvests. One of the potentially damaging Plant Disrupting Organisms is pests, whose presence in chili plants is very diverse. The life cycle and eating activities are very detrimental to farmers because it will reduce the yield of chili plants. The purpose of this study is to find out the diversity of pest types and to determine the rate of attack from fruit fly pests (Bactrocera dorsalis) on the curly red chili plant (Capsicum annum L.). Research has been carried out in Cabeyan Village, Bendosari district, Sukoharjo. October 1, 2020 – February 28, 2021. The study used observational, descriptive, and interview methods. Data collection is done directly and sampling using random sampling methods. In this study found several types of pests consisting of 12 species divided into 11 species into phylum Artropoda and 1 Species of Phylum Mollusca. As well as the rate of attack of fruit flies (Bactrocera dorsalis) with the highest average intensity of attack at 76% of the attack scale is very heavy.